2006
DOI: 10.1021/ja057316x
|View full text |Cite
|
Sign up to set email alerts
|

Conductance of Single Alkanedithiols:  Conduction Mechanism and Effect of Molecule−Electrode Contacts

Abstract: The conductance of single alkanedithiols covalently bound to gold electrodes has been studied by statistical analysis of repeatedly created molecular junctions. For each molecule, the conductance histogram reveals two sets of well-defined peaks, corresponding to two different conductance values. We have found that (1) both conductance values decrease exponentially with the molecular length with an identical decay constant, beta approximately equal to 0.84 A(-1), but with a factor of 5 difference in the prefact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

76
699
6

Year Published

2007
2007
2015
2015

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 493 publications
(782 citation statements)
references
References 45 publications
(76 reference statements)
76
699
6
Order By: Relevance
“…A similar study for an octanedithiol-Au junction has also been reported, 89 and for an asymmetric junction they found the breaking force of the Au-thiol bond to be 0.4-0.8 nN. Other experiments using the same molecule 84,85 reported a breaking force of 1.5 nN, which is very similar to the breaking force of a Au-Au bond, therefore, leading to the conclusion that the junction might break at the Au-Au bond and also indicating the presence of Au-thiolate instead of Au-thiol junctions. In summary, we find that the dissociative reaction of methanethiol and BDT2H on Au(111) is energetically unfavorable.…”
Section: Stability Study Of Thiol-terminated Molecules On a Au(111) Fsupporting
confidence: 65%
“…A similar study for an octanedithiol-Au junction has also been reported, 89 and for an asymmetric junction they found the breaking force of the Au-thiol bond to be 0.4-0.8 nN. Other experiments using the same molecule 84,85 reported a breaking force of 1.5 nN, which is very similar to the breaking force of a Au-Au bond, therefore, leading to the conclusion that the junction might break at the Au-Au bond and also indicating the presence of Au-thiolate instead of Au-thiol junctions. In summary, we find that the dissociative reaction of methanethiol and BDT2H on Au(111) is energetically unfavorable.…”
Section: Stability Study Of Thiol-terminated Molecules On a Au(111) Fsupporting
confidence: 65%
“…7,25,26 We consider two possibilities: (1) the connection is straight with an optimized Au-S bond length, as shown in Fig. 5 (a) for a BDT molecule, which is possible to occur when the STM tip is pulled from the gold surface, as suggested in Refs.…”
Section: Resultsmentioning
confidence: 99%
“…7,25,26,27,28,29,30,31,32,33,34 We also consider two different molecule-lead contacts, through a flat Au surface or through an apex Au atom, both of which are also possible to occur in experiments. 7,25,26,27,28,33,34 We adopt a single-particle Green function method 35,36 combining a Landauer formula with ab initio DFT 37 electronic structure calculation to investigate the electron transport through the junctions. 35,36,38 In practice, we divide an infinitely long Au-molecule-Au system into three parts: left lead, right lead, and device region which contains the molecule and large parts of the Au leads (see, for instance, Fig.…”
Section: Computationmentioning
confidence: 99%
“…[18][19][20][21][22][23][24] A thiol group is most commonly used to build a strong chemical link between the single molecules and the Au electrodes in molecular junctions. The conductance of such single-molecule junctions is typically several orders of magnitude smaller than G 0 =2e 2 / h ͑the conduc-tance quantum͒.…”
Section: Introductionmentioning
confidence: 99%
“…20,[22][23][24]27,28 Thus, in transport experiments, for a given bonding type, several binding sites are plausible, and hundreds of fabricated samples of the bonding type give rise to a histogram of conductance for given gate voltage or a series of current-voltage curves. In the present study, we take into account five different bonding types between an Mn 12 and Au electrodes, and for each bonding type, some representative interface geometries are examined.…”
Section: Introductionmentioning
confidence: 99%